Research on residual stress inside Fe-Mn-Si shape memory alloy coating by laser cladding processing - 鞠恒 林成新 张佳琪 刘志杰 (Optoelectronics letters, 2016)
The stainless Fe-Mn-Si shape memory alloy（SMA） coating was prepared on the surface of AISI 304 stainless steel. The principal residual stress measured by the mechanical hole-drilling method indicates that the Fe-Mn-Si SMA cladding specimen possesses a lower residual stress compared with the 304 stainless steel cladding specimen. The mean stress values of the former and the latter on 10-mm-thick substrate are 4.751 MPa and 7.399 MPa, respectively. What＇s more, their deformation values on 2-mm-thick substrate are about 0° and 15°, respectively. Meanwhile, the variation trend and the value of the residual stress simulated by the ANSYS finite element software consist with experimental results. The X-ray diffraction（XRD） pattern shows ε-martensite exists in Fe-Mn-Si SMA coating, which verifies the mechanism of low residual stress. That＇s the γ→ε martensite phase transformation, which relaxes the residual stress of the specimen and reduces its deformation in the laser cladding processing.